Penanganan Kesehatan Jiwa di Jakarta, 1960-an–1970-an - Mustaqim Aji Negoro (Lembaran Sejarah, 2022)
This study examines the development of mental health management in Jakarta between the 1960s and 1970s. The discussion focuses on the question of how the process of expanding mental health services in Jakarta in the 1960s to 1970s took place. This is important because it has been in these years that awareness – both from the government and the private sector – emerged and developed rapidly in Jakarta. The majority of sources used in this paper are news in contemporary newspapers and magazines. Through this search, historical facts regarding the handling of mental health in Jakarta are collected and arranged chronologically.